The micromorphological and anatomical properties of Onosma angustissimum Hausskn. & Bornm. and O. cassium Boiss. (Boraginaceae) (Bangladesh Journal of Plant Taxonomy, 2010)
The micromorphological and anatomical properties of Onosma angustissimum Hausskn. & Bornm. and O. cassium Boiss. were investigated. O. angustissimum is an endemic species. All examined taxa had secondary root structure. Crystals were seen in the stem and leaves of two species. Epidermal cells containing crystal needles were observed in O. cassium. Studied Onosma species had isobilateral type of leaves. Stomata were anisocytic and anomocytic. Glandular and eglandular trichomes especially porrect-stellate and simple trichomes were densely seen on the both upper and lower epidermis of leaves in two species. Stomata index was different in O. cassium from O. angustissimum.Keywords: Boraginaceae; Onosma; Morphology; Anatomy; LM; SEMDOI: 10.3329/bjpt.v17i1.5386Bangladesh J. Plant Taxon. 17(1): 1-8, 2010 (June)